Examining the Influence of Entrepreneurial Experiential Learning, Entrepreneurial Self-Efficacy and Gender on Entrepreneurial Intentions of Students: A Study of Higher Educational Institutions - Taneja, Mohit (Thapar Institute of Engineering & Technology, 2023)
The current investigation aims at examining the influence of entrepreneurial experiential learning, entrepreneurial self-efficacy, and entrepreneurial attitude on entrepreneurial intention concerning to the higher educational students. Moreover, the direct and indirect relationship (through lens of entrepreneurial self-efficacy) of experiential learning with entrepreneurial intention was observed to have a comprehensive viewpoint. We have also considered above linkage in terms of gender, separate conceptual models were designed for males and females. A structured questionnaire was used for collecting data from the students who were actually enrolled under entrepreneurial courses in their respective universities. This research has used SEM (structural equation modeling), partial least square (PLS) to observe the relationship of above mention determinants with entrepreneurial intention. The data were collected from 669 students enrolled under various entrepreneurial courses provided by certain higher educational institutes reside in Punjab, Haryana and National capital region (NCR). The results showed that the direct and indirect relationship of experiential learning with entrepreneurial intention were significant and positive. While through β-value it was observed that the relationship gets enhanced among experiential learning and entrepreneurial intention when entrepreneurial self-efficacy mediates this association. Furthermore, the direct relationship between entrepreneurial attitude and entrepreneurial intention was found to be significant and positive. The gender-wise results showed that the direct relationship of experiential learning and entrepreneurial intentions were strong and positive in both the case of males and females. However, the magnitude of the β-value was greater for females than for males. The indirect influence of experiential learning on entrepreneurial intention via entrepreneurial self-efficacy was significant in both the cases. Whereas it was found that relatively male’s entrepreneurial intentions through entrepreneurial self-efficacy were more than of female students. Therefore, the present investigation adds to the body of knowledge concerning to entrepreneurship in various manner. First it focuses our attention on entrepreneurial experiential learning in framing entrepreneurial intentions of the students. Secondly, it also suggests that the relationship of experiential learning and entrepreneurial intention become stronger with mediation of entrepreneurial self-efficacy. Thus, it should also be deduced that the policy makers in the field entrepreneurship, should frame entrepreneurial education policies gender-wise.
Keywords: Entrepreneurial Experiential Learning; Entrepreneurial Self-Efficacy; Entrepreneurial Intentions; Higher Educational Institutions